SIRT7 is an RNA-activated protein lysine deacylase - Tong, Zhen (ACS Chem Biol, 2016)
Mammalian SIRT7 is a member of the sirtuin family that regulate multiple biological processes including genome stability, metabolic pathways, stress responses, and tumorigenesis. SIRT7 has been shown to be important for ribosome biogenesis and transcriptional regulation. SIRT7 knockout mice exhibit complications associated with fatty liver and increased aging in hematopoietic stem cells. However, the molecular basis for its biological function remains unclear, in part due to the lack of efficient enzymatic activity in vitro. Previously we have demonstrated that double-stranded DNA could activate SIRT7’s deacetylase activity in vitro, allowing it to deacetylate H3K18 in the context of chromatin. Here we show that RNA can increase the catalytic efficiency of SIRT7 even better and that SIRT7 can remove long chain fatty acyl groups more efficiently than removing acetyl groups. Truncation and mutagenesis studies revealed residues at both the amino and carboxyl termini of SIRT7 that are involved in RNA-binding and important for activity. RNA immunoprecipitation-sequencing (RIP-seq) identified ribosomal RNA (rRNA) as the predominant RNA binding partners of SIRT7. The associated RNA was able to effectively activate the deacetylase and defatty-acylase activities of SIRT7. Knockdown of SIRT7 increased the lysine fatty acylation of several nuclear proteins based on metabolic labeling with an alkyne-tagged fatty acid analog, supporting that the defatty-acylase activity of SIRT7 is physiologically relevant. These findings provide important insights into the biological functions of SIRT7, as well as an improved platform to develop SIRT7 modulators.